A membraneless hydrogen peroxide fuel cell using Prussian Blue as cathode material - Shaegh, Seyed Ali Mousavi (2013)
This communication describes the exploitation of Prussian Blue, ferric ferrocyanide (Fe4III[FeII(CN)6]3), for the cathode side in a single-chamber membraneless fuel cell running on hydrogen peroxide (H2O2) as both fuel and oxidant. An open-circuit voltage (OCV) of 0.6 V has been obtained, which could be the highest OCV with H2O2 ever reported. The maximum power density was 1.55 mW cm−2 which showed a stable long-term operation in acidic media.